If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 9 = 30 + -6x Reorder the terms: 9 + -3x = 30 + -6x Solving 9 + -3x = 30 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 9 + -3x + 6x = 30 + -6x + 6x Combine like terms: -3x + 6x = 3x 9 + 3x = 30 + -6x + 6x Combine like terms: -6x + 6x = 0 9 + 3x = 30 + 0 9 + 3x = 30 Add '-9' to each side of the equation. 9 + -9 + 3x = 30 + -9 Combine like terms: 9 + -9 = 0 0 + 3x = 30 + -9 3x = 30 + -9 Combine like terms: 30 + -9 = 21 3x = 21 Divide each side by '3'. x = 7 Simplifying x = 7
| 2c/10=24 | | (5c+6)(5c-6)=0 | | 2x^2-4x-44=0 | | 53a-143=42a+8 | | 3x=6-x | | 18-t/20=-9 | | 3s/5=-21 | | x^2-15x+9=0 | | n(n-6)=7 | | 25x(x+4)=10x-81 | | 17b+3=-422 | | 18=18y-18 | | 3c+45=7.2-6c | | 7m^2-2m+2=0 | | 21=6m-9 | | -7+z/4=0 | | -7m^2+2m-2=0 | | (x-10)+(x+2)=90 | | 6x+(-3)=117 | | 4(y+7)-7y=37 | | 6s-27=-19+4s | | 8x-143=-127 | | 9n-26=9+4n | | 436x-789=-571 | | 23x^2-20=0 | | -13x+28=-11 | | Y^2-.6y+.1=0 | | Y^2-.6y+.1111111111=0 | | 6x+18=4x+2 | | 3b(4-2b)-6b=-b(6b+7)+104 | | 12x+(-18)=66 | | -5x+13=58 |